PENGARUH MOTIVASI BELAJAR DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA SMA NEGERI DI KOTA TUBAN - Darmawati, Joenita (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aims to determine 1) the influence of motivation on learning achievement, 2) the influence of learning style on learning achievement, and 3) the influence of motivation and learning styles on learning achievement. The populations were 379 senior high school students of grade XI in Tuban. Samples were taken by employing simple random sampling technique yielding in 195 students. Data were collected by using questionnaires. Data was analyzed by using the multiple linear regression analysis. Finding indicates that the partial test (t test) concluded the significant effect of motivation on students achievement and the significant effect of learning styles on academic achievement. Based on F test, it was concluded that both motivation and learning styles simultaneously affect students achievement. Consequently, students are suggested to know more about their own learning styles to optimize their learning achievement. Teachers are also advised to design their instruction in such a way that it accommodates all the learning styles.